Analisis Keterlambatan dalam Pelaksanaan Proyek Konstruksi Rumah Hunian Dempsey Hill, Citraland Utara, Kota Surabaya - Yafie Abdillah Akbar; Ridho Bayu Aji; Gentur Prihartono; Muhammad Sigit Darmawan; Budi Suswanto (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This journal examines the factors that have the potential to cause delays in the implementation of the Dempsey Hill residential housing construction project, North Citraland, Surabaya. Projects managed by CV. Tirta Kusuma has a target of completion in 10 months, but there are indications of delays that affect the schedule and costs. This study aims to identify and analyze the dominant factors causing delays, such as project management, material procurement, and human resources. The methods used include observation, questionnaire distribution, and literature study. The results of this analysis are expected to provide recommendations to improve time management, resource efficiency, and control of future construction projects. The results of data analysis in this study indicate that project delays are primarily caused by material delays and errors in work execution, as concluded based on the results of factor analysis.